PROBLEMATIKA PEMBELAJARAN IDAFAH PADA PRODI PBA IAIN BONE (Suatu Tinjauan Nahwu) - B, Amir (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2018)
The quality of learning Arabic at IAIN Bone still requires perfection. That means there are still many problems found such as from the aspect of teaching, students, method and the media. From the method aspect, lecturers tend to maintain the old method compared to exploring various methods that have been suggested by researchers in learning Arabic, in this case is Idafah. This tendency is one of the problem factors in understanding Arabic (Idafah). Learning Arabic, still desperately needs new innovations, because most of them (students) are khirrij (luaran) from public schools that do not have basic or even some who have never learned Arabic at all. Apart from that, the problems that are obtained are lack of facilities and infrastructure, facilities, language laboratories.